Bonded Repair of Composite Structures; A Finite Element Approach - Odi, A. R. A. (Department of Materials and Medical Sciences, 2009)
This thesis addresses the issues surrounding the application of the finite element method to analyse composite structure repairs with an emphasis on aircraft applications. A comprehensive literature survey has been carried out for this purpose and the results are presented. A preliminary study and a comparative study of different modelling approaches have been completed. These studies aim to explore and identify the problems in modelling repairso n simplec ompositep anelsw ith speciala ttention given to adhesivem odelling. Three modelling approaches have been considered: Siener's model which is an extension of the traditional plane strain 2D model used for adhesively bonded joints, Bait's model which is a promising new approach and a full 3D model. These studies have shown that these methods are complementary providing a different insight into bonded repairs. They have also highlighted the need for a new modelling approach which will provide an overall view of bonded repairs. Improved modelling approachesh ave been developedf or externallyb onded patch and flush repairs. These models enable the study of adhesive failure as well as composite adherendf ailures.T hesea pproachesh aveb eena ppliedt o real repairs and the predicted results compared to experimental data. Four case studies have been conducted: external bonded patch repairs to composite plates, a scarf joint for bonded repairs, a flat panel repaired with a scarfed patch and a repaired curved panel. These case studies have shown that bonded repairs to composite structures can be analyseds uccessfullyu sing PC-basedc ommercialf inite elementc odes.
Keywords: Structural analysis (Engineering); Finite element method; Matrices; Composite materials - Cracking; Composite materials - Corrosion